Use of morphological characteristics for genetic purity evaluation of hybrid corn seed - Pinho, Édila Vilela de Resende Von; Pinho, Renzo Garcia Von; Cicero, Silvio Moure (Pesquisa Agropecuaria Brasileira, 1997)
In hybrid corn seed production fields, the incomplete removal of the female parental tassels which liberates its polen promotes the occurence of selfing, the main source of genetic contamination. The present work had the aim of rising morphological characteristics that could be used as markers to identify seeds derived from the selfed female parental mixed in hybrid seed lots. Hybrid seeds and selfed female parental seeds of the single hybrid C 901, the three way hybrid C 808A and the double-cross hybrids C 425 and C 701 were produced. Evaluations were carried out by different investigators on the stages of seedling, plants with 5-7 leaves, harvest and postharvest. The percentage of errors and the standard deviation of the results observed on the four replications of the three investigators were calculated. To verify the deviation significances of the normal curve that occurred during the process of evaluation of the three investigators, the chi-square test (χ2) was used. It was possible to separate, through morphological characteristics, the plants selfed out of hybrid plants, in three out of four cultivars studied. The development stage most apropriate to evaluate the genetic purity has varied with the hybrids.